2015
DOI: 10.1111/cea.12515
|View full text |Cite
|
Sign up to set email alerts
|

Basophil allergen threshold sensitivity and component‐resolved diagnostics improve hazelnut allergy diagnosis

Abstract: CD-sens and component-resolved diagnostics to hazelnut, used separately or in combination, may improve the diagnostic accuracy and safety and reduce overdiagnosis of hazelnut allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 23 publications
1
68
1
1
Order By: Relevance
“…The specificity of the BAT ranged between 77% and 100% in other studies (Table IV). 11, 67, 68, 69, 70, 71, 72, 73 The BAT with single allergen components can potentially improve its diagnostic accuracy, but further research studies are needed 72, 74, 75. The BAT has been shown to be potentially useful in identifying the culprit allergen in cases of pollen-food allergy syndrome (PFAS),71, 76, 77 allergy to red meat, 78 or food-dependent exercise-induced anaphylaxis 79 .…”
Section: In Vitro Tests For Ige-mediated Food Allergymentioning
confidence: 99%
“…The specificity of the BAT ranged between 77% and 100% in other studies (Table IV). 11, 67, 68, 69, 70, 71, 72, 73 The BAT with single allergen components can potentially improve its diagnostic accuracy, but further research studies are needed 72, 74, 75. The BAT has been shown to be potentially useful in identifying the culprit allergen in cases of pollen-food allergy syndrome (PFAS),71, 76, 77 allergy to red meat, 78 or food-dependent exercise-induced anaphylaxis 79 .…”
Section: In Vitro Tests For Ige-mediated Food Allergymentioning
confidence: 99%
“…They could show that the BAT adds safety information if sIgE and DBPCFC results were controversial. Thus, the BAT might be useful if clinical history, SPT and/or sIgE measurement are inconsistent or in addition an oral food challenge is not possible [42]. Furthermore, the use of recombinant allergens in the BAT might have added value in discriminating between clinically relevant and mere sensitization [44, 45] and should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…By an in‐vitro dose‐response allergen stimulation of the basophils, their allergen threshold sensitivity, CD‐sens 16 can be accurately determined. Studies have shown that CD‐sens correlates significantly with bronchial allergen threshold sensitivity 9 , nasal allergen challenge 14, 18 , and oral food challenge 15, 19, 20 .…”
Section: Discussionmentioning
confidence: 99%